Real-world effectiveness of voxilaprevir/velpatasvir/sofosbuvir in patients following DAA failure - Graf, Christiana; D’Ambrosio, Roberta; Degasperi, Elisabetta; Paolucci, Stefania; Llaneras, Jordi; Vermehren, Johannes; Dultz, Georg; Peiffer, Kai-Henrik; Finkelmeier, Fabian; Herrmann, Eva; Zeuzem, Stefan; Buti, Maria; et al. (JHEP reports, 2024)
Voxilaprevir/velpatasvir/sofosbuvir (VOX/VEL/SOF) is highly effective for re-treatment of direct-acting antiviral (DAA)-experienced patients with chronic HCV infection. In the present study, predictors of virologic treatment response were analyzed in an integrative analysis of three large real-world cohorts. Consecutive patients re-treated with VOX/VEL/SOF after DAA failure were enrolled between 2016 and 2021 in Austria, Belgium, Germany, Italy, Spain and Switzerland. A total of 746 patients were included: median age was 56 (16-88) years and 77% were male. Most patients were infected with HCV genotype 1 (56%) and 3 (32%). 86% of patients carried resistance-associated substitutions in the NS3, NS5A or NS5B regions. Overall, 95.4% (683/716) of patients achieved a sustained virologic response. Treatment effectiveness was significantly affected by advanced liver disease (p <0.001), hepatocellular carcinoma (p <0.001), higher baseline ALT levels (p = 0.02), HCV genotype 3 (p <0.001), and prior VEL/SOF treatment (p = 0.01). In a multivariate analysis, only HCV genotype 3, hepatocellular carcinoma and cirrhosis turned out to be independent predictors of treatment failure. Resistance-associated substitutions, as well as the presence of rare genotypes, did not impact treatment outcome. The effectiveness of rescue therapy with glecaprevir/pibrentasvir and SOF, with or without ribavirin, for 12 to 24 weeks was found to be high (100%). Infection with HCV genotype 3, the presence of liver cancer and cirrhosis are independently associated with failure of VOX/VEL/SOF re-treatment. It is unclear whether the addition of ribavirin and/or extension of treatment duration may be effective to avoid virologic relapse on VOX/VEL/SOF. However, rescue treatment with glecaprevir/pibrentasvir+SOF seems to be effective. Representative data on the effectiveness of voxilaprevir/velpatasvir/sofosbuvir (VOX/VEL/SOF) in clinical practice are still scarce and the collection of a larger number of patients with difficult-to-treat cofactors including the assessment of resistance-associated substitution profiles is required before more specific recommendations for optimal re-treatment in these patients can be given. Thus, we aimed to analyze treatment effectiveness and predictors of virologic response to VOX/VEL/SOF in an integrative analysis of three large real-word cohorts. The study results, derived from a multicenter cohort consisting of 746 patients, demonstrated that re-treatment with VOX/VEL/SOF is an effective salvage therapy associated with an overall per protocol sustained virologic response rate of 95%. Hepatocellular carcinoma onset, cirrhosis and HCV genotype 3 were identified as independent negative predictors of treatment response, whereas resistance-associated substitutions, as well as rare genotypes and chimera, did not impact sustained virologic response rates following re-treatment with VOX/VEL/SOF. [Display omitted] •Overall high effectiveness of VOX/VEL/SOF was demonstrated in an integrative analysis of large real-world studies.•Significantly lower SVR rates were observed in patients with GT3, advanced liver disease, HCC onset and VEL/SOF pretreatment.•RASs as well as rare genotypes and chimera did not impact SVR rates following VOX/VEL/SOF re-treatment.•Cirrhosis, GT3 and HCC onset were identified as independent negative predictors of treatment response to VOX/VEL/SOF.